Ultra‐Confined Catalytic Growth Integration of Sub‐10 nm 3D Stacked Silicon Nanowires Via a Self‐Delimited Droplet Formation Strategy (Small 42/2022). Issue 42 (20th October 2022) - Hu, Ruijin; Liang, Yifei; Qian, Wentao; Gan, Xin; Liang, Lei; Wang, Junzhuan; Liu, Zongguang; Shi, Yi; Xu, Jun; Chen, Kunji; Yu, Linwei
Abstract : Droplet Control In article number 2204390, Linwei Yu and co‐workers successfully demonstrate stacked growth integration of ultrathin silicon nanowires, with width and height of W nw = 9.9 ± 1.2 nm (down to 8 nm) and H nw = 18.8 ± 1.8 nm approaching to the critical‐dimension of 10 nm technology node, thanks to a self‐delimited droplet control strategy, with tunable channel cross‐sections, which are ideal candidates for monolithic 3D integration of logic‐in‐memory and neuromorphic applications.